Biomass in situ conversion to Fe single atomic sites coupled with Fe2O3 clusters embedded in porous carbons for the oxygen reduction reaction. Issue 39 (2nd October 2020) - Lei, Ying; Yang, Fuwen; Xie, Huaming; Lei, Yongpeng; Liu, Xingyong; Si, Yujun; Wang, Honghui
Abstract : Small metal clusters have received increasing attention due to their attractive and superior performance in electrocatalytic energy conversion. Abstract : Small metal clusters have received increasing attention due to their attractive and superior performance in electrocatalytic energy conversion. However, the design and synthesis of well-dispersed metal clusters is a great challenge owing to their ease of aggregation. Here, we develop a biomass in situ conversion strategy to synthesize Fe single atomic sites (Fe–N4 ) combined with ultra-small Fe2 O3 nanoclusters embedded in N, S codoped porous carbons (FeSA /FeONC /NSC) for the oxygen reduction reaction (ORR). The resultant FeSA /FeONC /NSC exhibits a high half-wave potential ( E 1/2 = 0.86 V vs. RHE) and an outstanding kinetic current density at 0.80 V ( J k = 32.15 mA cm −2 ), which even surpasses those of commercial Pt/C ( E 1/2 = 0.85 V, J k = 16.5 mA cm −2 ). Atomic level dispersed Fe–N4 sites integrated with Fe2 O3 clusters embedded in N, S-mediated carbon are mainly responsible for the excellent ORR activity. More importantly, the assembled Zn–air battery can output a prominent power density of 179.0 mW cm −2 and energy density of 837.4 W h kg −1 along with robust stability, outperforming the commercial Pt/C and most non-platinum catalysts. This work opens up an avenue for biomass in situ conversion into non-precious metal electrocatalysts for energy conversion and storage technologies.